CARVING SUCCESSFUL PUBLIC SPACES ALONG HISTORIC URBAN RIVERSCAPES - Mat Nayan, Nadiyanti; Khamis, Mohd Khedzir; S Jones, David (PLANNING MALAYSIA, 2024)
Recreational activities along urban waterways has gained popularity since the 1970s and efforts are underway to enhance public access to waterfront locations. Consequently, this resurgence has spurred the development of diverse public open spaces along riverbanks, offering various means of engagement with the river ecosystem. In the case of Kuala Lumpur, Malaysia, the historical significance of the confluence of Sungai Klang and Sungai Gombak dated back to the 1850s. This paper examines on how these historic urban rivers of Kuala Lumpur portrayed as a successful public space based on four qualities highlighted by the Project for Public Spaces: Sociability, Uses and Activities, Access and Linkages, as well as Comfort and Images. To study the applicability of these qualities, a comprehensive site observation was conducted using a checklist provided by the Project for Public Spaces. The findings from this case study confirmed the relevance of these criteria and underscore the significance of an integrated approach to foster successful public spaces, particularly in accentuating the unique attributes of historic urban rivers.